FORMULASI DAN PENENTUAN NILAI SPF (SUN PROTECTING FACTOR) SEDIAAN KRIM TABIR SURYA EKSTRAK ETANOL DAUN KEMANGI (Ocimum sanctum L.) - Isriany Ismail; Gemy Nastity Handayany; Dwi Wahyuni; Juliandri Juliandri (Jurnal Farmasi UIN Alauddin Makassar, 2014)
Now, it has starting the concept of re-using the natural materials to overcome and prevent disease (back to nature), one of those materials is the active ingredients from sunscreens. Basil leaves are used as samples in this study, because there are compounds in basil leaves (Phenolic, especially flavonoids and tannins) that presumed have an effect as a sunscreen, because it has a chromophore group which capable to absorb both UV rays, UV A and UV B. This study intends to determine the value of SPF from the cream of sunscreen preparation. The value of SPF is determined by using the method which developed by Mansur. The cream is made with a concentration of 0.03% (Formula I), 0.06% (Formula II), and 0.12% (Formula III). The results has shown that the Formula I with a 0.03% extract concentration has 5.21 SPF value; Formula II with a 0.06% extract concentration has 5.94 SPF value. Both of these formulas has been put into the mild level from category of sunscreen ability and formula III with a 0.12% extract concentration has 8.97 SPF value has been put into the maximal level from category of sunscreen ability.